2015
DOI: 10.5539/ijel.v5n5p99
|View full text |Cite
|
Sign up to set email alerts
|

The Sociolinguistic Dimensions of Code-Switching between Arabic and English by Saudis

Abstract: The neglected area of Arab speakers' verbal performance in mixed-sex contexts is the focus of this study. This paper attempts to contribute to this area by studying the frequency and type of code-switches from Arabic into English in the casual conversations of young bilingual Saudis. Findings indicate that Saudi females' style of speech was characterized by substantially more code-switching from Arabic into English particularly single noun and adjective switches than their male counterparts in both single and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Intra-sentential code switching is used when a speaker switches from one code to another using a phrase (Hoffman,1991;Ismail, 2015;Muysken, 2000). Such code switching often identified within Jun Bintang caption like in the following example.…”
Section: ) Intra-sentential Swicthingmentioning
confidence: 99%
“…Intra-sentential code switching is used when a speaker switches from one code to another using a phrase (Hoffman,1991;Ismail, 2015;Muysken, 2000). Such code switching often identified within Jun Bintang caption like in the following example.…”
Section: ) Intra-sentential Swicthingmentioning
confidence: 99%
“…The vast majority of the available CS speech corpora have covered Chinese-English [28,86,66,70,2], Hindi-English [34,82,87,90,78] and Spanish-English [88,33,82] language pairs. Less work has covered Arabic-English [54,46,47], Arabic-French [12,14], Frisian-Dutch [101], Mandarin-Taiwanese [69,68], Turkish-German [26], English-Malay [2], English-isiZulu [98] and Sepedi-English [73]. For Arabic CS, speech corpora are very limited in size as well as covered language-pairs.…”
Section: Cs Speech Corporamentioning
confidence: 99%
“…For Arabic CS, speech corpora are very limited in size as well as covered language-pairs. Ismail [54] collected an 89-minutes speech corpus by recording and transcribing informal dinner gatherings involving 6 participants. Amazouz et al [12] gathered a 7.5 hours of read speech from books and movie transcripts, as well as informal conversations, gathered from 20 speakers.…”
Section: Cs Speech Corporamentioning
confidence: 99%
“…Only two studies explored the linguistic gender-based differences among Saudi speakers. In one study, Ismail (2015) studied the frequency and types of code-switches from Arabic into English in young bilingual Saudis' casual conversations. She found that Saudi females code-switch more than males.…”
Section: Introductionmentioning
confidence: 99%